ANALISIS KUALITAS AIR SUNGAI ANCAR DALAM UPAYA BIOREMIDIASI PERAIRAN - Dharmawibawa, Iwan Doddy; Hunaepi, Hunaepi; Fitriani, Herdiyana (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
The purpose of this research is to know the characteristic 'water quality' river ancar Mataram city based on biological, chemical, and physics as bioremidiasi waters. The type of this research is descriptive explorative and research method used is survey, laboratory analysis, and case study, ie method of all aspects must be observed fully, while the data analysis is only valid for certain place and time period. The results showed that, overall observation and identification of 6 research sampling stations, 21 species were identified with four microlagae classes: Bacillariophyceae, Cyanopyceae, Chlorophyceae and Crysophyceae. Bacillariophyceae class is the class that has the most types, then Cyanophyceae, Chlorophyceae and Chrisophyceae. Factors supporting the growth of bologic components such as pH, temperature, light intensity, salinity with the range of each 7.2-8.3; 25-27 Â° C; 1011-1800 lux; 3-3.2%, nutrients (N and P), according to the microalgae living conditions which are the most primitive plant organisms that are small in size, live in all waters, both rivers and seawater.